Potential of Tyre Derived Geomaterial as Alternative Material in Gabion Type Retaining Wall - Abdullah, Amizatulhani (International Journal of Integrated Engineering, 2019)
The disposal of scrap tyre is a major problem in developing countries. Material recycling is adopted in order to promote safer disposal (beside conventional dump and thermal recycling). Tyre derived geomaterial (TDGM) are proposed to be used in construction of gabion type retaining wall to prevent slope failure that has been a serious geotechnical threat in many countries. The reason of choosing tyre is not only to help in reducing the stockpiling of scrap tyre generated in environmentally friendly way but also to reduce the dependency of gravel as the material to filled current gabion wall. In this study, various mixtures were considered in laboratory scale retaining wall namely, 100% gravel, 100% tyre and 50% of both materials. The retaining wall was functioned to retain a 60Âº of sand slope. The slope was then subjected to 0.8 mm/hour of artificial rainfall. The soil movement from commencement of the test until the slope failed was recorded. Several tests were carried out to determine basic characteristics (grains size distribution and standard Proctor test) of materials used in the study were conducted beforehand. The results showed that TDGM was able to mitigate slope failure as effective as using gravel. No significant horizontal movements were recorded compared to the slope without any countermeasure. However, slight settlement of gabion wall was recorded and need further testing for clarification.